Forensic accounting for dummies - Kass-Shraibman, Frimette; Sampath, Vijay S. (Hoboken, NJ : Wiley Pub., 2011)
Forensic accountants investigate economic crimes, perform risk assessments, assist in all kinds of civil litigation, and provide expert testimony. This hands-on guide give you plain-English explanations of the concepts and methods of forensic accounting.
Includes index.
Keywords: Forensic accounting; Fraud investigation; Fraud -- Prevention